STRATEGI SATUAN POLISI PAMONG PRAJA DALAM PENERTIBAN PROSTITUSI DI KOTA MANADO PROVINSI SULAWESI UTARA - William Paulus Budiman, Sandro; Satria Utama, Lalu (Journal of Innovation Research and Knowledge, 2025)
Prostitution in Manado City is still a problem that disturbs public peace and order, the Manado City government has regulated the prohibition of prostitution in Manado City Regional Regulation No. 2 of 2019 Article 25 in the hope of reducing prostitution practices that occur in Manado City. However, until now prostitution in Manado City with various forms is still rampant. Specifically, this research examines how Satpol PP's strategy in enforcing prostitution practices. This research was conducted because of the rampant practice of prostitution, both directly in public spaces and through online media, which is a challenge for the local government. Objective: To explain how the Manado City Satpol PP strategy in enforcing prostitution practices Method: This research uses descriptive qualitative method by describing facts in the field and data collection techniques using observation, interviews and documentation and data retrieval techniques using purposive sampling and snowball sampling. Based on the results/findings: it was found that the strategy applied by Satpol PP Manado City in controlling prostitution has not run optimally and consistently. This can be seen from the direct control efforts that have been carried out such as raids and coaching which have not been carried out consistently so that they do not have a significant deterrent effect. The lack of implementation is due to the fact that prostitution control has not been a priority program of the government, which has an impact on budget allocations that are inconsistent from year to year. In addition, the obstacle faced in controlling prostitution is the development of online prostitution practices that are increasingly widespread, which have not been adjusted with supporting facilities and infrastructure Public order and compliance are still low as a result of inconsistent enforcement. Conclusion: the strategy of controlling prostitution needs to be reviewed and adjusted to the changing dynamics of prostitution practices. More modern strategic efforts and consistent enforcement are needed so that prostitution in Manado City can be significantly reduced